Pengaruh Pengendalian Anggaran pada Senjangan Anggaran dan Orientasi Jangka Pendek Manajer - Novitasari, Ninis; Wirama, Dewa Gede (E-Jurnal Akuntansi; Vol 13 No 3 (2015), 2016)
Budgetary control is a means of control in an organization with the establishment of standards targets regarding revenue and expenditure as well as continuous monitoring of performance by comparing the budget with its best estimate . With the control of the budget raises two consequences that budgetary slack and short-term orientation managers. This study aims to determine the effect on the budgetary control budgetary slack and short-term orientation in the manager-star hotels in Badung. Three star hotels and above chosen as the study site because in general with the classification utilizing the budget as a management tool. Samples are taken as many as 110 managers of 67 luxury hotels in Badung, with purposive sampling method. The analysis technique used is a simple linear analysis. These results indicate that the negative effect on the budgetary control budgetary slack and positive effect on short-term orientation managers. With the tight budget control, the slack in the budget can be minimized, but on the other hand tight budget control lead managers will be more oriented towards short-term performance and will hamper long-term innovations.
Keywords: budgetary control; budgetary slack; short-term orientation manager